Dissemination of Two Methicillin-Resistant Staphylococcus aureus Clones Exhibiting Negative Staphylase Reactions in Intensive Care Units - Hsueh, Po-Ren (American Society for Microbiology, 1999)
From December 1997 to March 1998, 25 methicillin-resistant Staphylococcus aureus (MRSA) isolates exhibiting negative Staphylase (Oxoid Ltd., Basingstoke, England) reactions were identified from various clinical specimens from 13 patients in six intensive care units (ICUs) or in wards following a stay in an ICU at the National Taiwan University Hospital. The characteristics of these isolates have not been previously noted in other MRSA isolates from this hospital. Colonies of all these isolates were grown on Trypticase soy agar supplemented with 5% sheep blood and were nonhemolytic and unpigmented. Seven isolates, initially reported as Staphylococcus haemolyticus (5 isolates) and Staphylococcus epidermidis (2 isolates) by the routine identification scheme and with the Vitek GPI system (bioMerieux Vitek, Inc., Hazelwood, Mo.), were subsequently identified as S. aureus by positive tube coagulase tests, standard biochemical reactions, and characteristic cellular fatty acid chromatograms. The antibiotypes obtained by the E test, coagulase types, restriction fragment length polymorphism profiles of the staphylococcal coagulase gene, and random amplified polymorphic DNA patterns generated by arbitrarily primed PCR of the isolates disclosed that two major clones disseminated in the ICUs. Clone 1 (16 isolates) was resistant to clindamycin and was susceptible to trimethoprim-sulfamethoxazole (TMP-SMZ) and was coagulase type II. Clone 2 (eight isolates) was resistant to clindamycin and TMP-SMZ and was coagulase type IV. These two epidemic clones from ICUs are unique and underline the need for caution in identifying MRSA strains with colonial morphologies not of the typical type and with negative Staphylase reactions.